My butch career: A memoir - Newton, Esther (Duke University Press, 2018)
During her difficult childhood, Esther Newton recalls that she “became an anti-girl, a girl refusenik, caught between genders,” and that her “child body was a strong and capable instrument stuffed into the word ‘girl.’” Later, in early adulthood, as she was on her way to becoming a trailblazing figure in gay and lesbian studies, she “had already chosen higher education over the strongest passion in my life, my love for women, because the two seemed incompatible.” In My Butch Career Newton tells the compelling, disarming, and at times sexy story of her struggle to write, teach, and find love, all while coming to terms with her identity during a particularly intense time of homophobic persecution in the twentieth century. Newton recounts a series of traumas and conflicts, from being molested as a child to her failed attempts to live a “normal,” straight life in high school and college. She discusses being denied tenure at Queens College—despite having written the foundational Mother Camp—and nearly again so at SUNY Purchase. With humor and grace, she describes the influence her father Saul's strong masculinity had on her, her introduction to middle-class gay life, and her love affairs—including one with a well-known abstract painter and another with a French academic she met on a spur-of-the-moment trip to Mexico and with whom she traveled throughout France and Switzerland. By age forty, where Newton's narrative ends, she began to achieve personal and scholarly stability in the company of the first politicized generation of out lesbian and gay scholars with whom she helped create gender and sexuality studies. Affecting and immediate, My Butch Career is a story of a gender outlaw in the making, an invaluable account of a beloved and influential figure in LGBT history, and a powerful reminder of just how recently it has been possible to be an openly queer academic.
Keywords: amériques; approches et analyses; autobiographie; butch; histoire et politique; hétérosexisme; identités LGBTQIA2+; queer; ressource en ligne; régions géographiques; sexualité; systèmes d'oppressions; thématiques; travail; violences; états-unis

BLOOD UNDER THE BRIDGE: REFLECTIONS ON “THINKING SEX” - Rubin, Gayle (GLQ: A Journal of Lesbian and Gay Studies, 2011)
This article reflects on the intellectual and political circumstances of the publication of Gayle Rubin's 1984 essay “Thinking Sex: Notes for a Radical Theory of the Politics of Sexuality.” In particular, the article considers the context of the feminist “sex wars” of the late 1970s and early 1980s, offering a detailed account of several of the period's key events, publications, and debates. The article also reflects on the relation between this moment in the history of feminism and the history of GLBT and queer scholarship over the past several decades.
Keywords: 1900-1999; 1960-1969; 1970-1979; LGBTQIA2+; amériques; approches et analyses; cours; discipline; discours dominant; féminisme pro-sexe; histoire et politique; militance; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sex wars; soc2014; systèmes d'oppressions; thématiques; travail; violences; états-unis; études de genres

Money, myths, and change: the economic lives of lesbians and gay men - Badgett, Mary Virginia Lee (Worlds of desire, 2001)
How does the standard of living of gay men and lesbians compare with that of heterosexuals? Do homosexuals make financial and family decisions differently? Why are the professional lives of gay men and lesbians dissimilar from those of heterosexuals? Or do they even differ? Have gay people benefited from the recent economic boom? Or have public policies denied them their fair share? Money, Myths, and Change provides new answers to these complex questions. This is the first comprehensive work to explore the economic lives of gays and lesbians in the United States. M. V. Lee Badgett weaves through and debunks common stereotypes about gay privilege, income, and consumer behavior. Studying the ends and means of gay life from an economic perspective, she disproves the assumption that gay men and lesbians are more affluent than heterosexuals, that they inspire discrimination when they come out of the closet, that they consume more conspicuously, that they enjoy a more self-indulgent, even hedonistic lifestyle. Badgett gets to the heart of these misconceptions through an analysis of the crucial issues that affect the livelihood of gay men and lesbians: discrimination in the workplace, denial of health care benefits to domestic partners and children, lack of access to legal institutions such as marriage, the corporate wooing of gay consumer dollars, and the use of gay economic clout to inspire social and political change. Both timely and readable, Money, Myths, and Change stands as a much-needed corrective to the assumptions that inhibit gay economic equality. It is a definitive work that sheds new light on just what it means to be gay or lesbian in the United States.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; capitalisme; cours; discipline; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; premier cycle; périodes historiques; queer; rapports sociaux de sexe; régions géographiques; shm4000; systèmes d'oppressions; thématiques; travail; états-unis

Sky's the limit: The operations, renovations and implications of a Montréal gay bar - Allan, James (Université McGill, 1997)
Sky, un Hméga-club" en plein essor situé au coeur du village gai de Montréal, représente plusieurs tendances au sein des clubs et des villages gais de l'Amérique du Nord à la fin du XXième siècle. Ce projet aborde les opérations quotidiennes du Sky, en tenant compte de son architecture complexe, de ses pratiques de gestion, et de sa popularité à l'intérieur du village ainsi que des ramifications théoriques de cet établissement pour la communauté gaie et pour la culture des clubs de nuit en général. Au plan théorique, ce complexe récréatif présentement en expansion constitue un phénomène ni complètement opprimant, ni entièrement libérateur. Bien que le Sky offre certains des avantages d'un "méga-club" pour la communauté gaie--plus grande diversité, accessibilité, et communauté--il possède également les désavantages de ces établissements: la concentration du pouvoir économique, une moins grande présence gaie dans les rues, et la promotion de certaines identités et cultures gaies plutôt que d'autres.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; amériques; approches et analyses; communication; discipline; environnement; espace sécuritaire; identités LGBTQIA2+; montréal; mémoires/thèses; périodes historiques; queer; ressource en ligne; régions géographiques; thématiques; travail